Centenary of Archives of Pathology & Laboratory Medicine: Its Conception, Gestation, Birth, Childhood, and Maturation - James R. Wright (Archives of Pathology & Laboratory Medicine, 2026)
Archives of Pathology & Laboratory Medicine is 100 years old this year. In this article, I describe the milieu into which Archives was conceived, then recount details of its gestation and birth, compare and contrast it with its siblings and cousins, and finally describe its growth and maturation. Throughout the 19th century, pathology was exclusively an academic discipline. During the first 2 decades of the 20th century, the opportunity for laboratorians to provide “clinical pathology” services directed at improving patient care appeared. In 1901, during the heyday of medical specialization, the American Medical Association created a Section on Pathology and Physiology, and in 1925 this section recommended that the American Medical Association establish a specialty journal. In January 1926, Archives was established with Ludvig Hektoen, MD, as editor. At about the same time, several other American pathology journals appeared on the horizon, with each filling different niches. Archives ’ publication mix was roughly half observational pathologic morphology and half experimental pathology. During the 1920s, America became the world leader in both surgical pathology and clinical pathology, allowing the journal to thrive. In 1984, the College of American Pathologists (CAP) became the journal’s co-sponsor and in 1995 CAP assumed its full fiscal, editorial, and operational responsibility. In 2009, Archives was voted the only pathology journal among the top 100 most influential journals of biology and medicine in the past 100 years by the Biomedical and Life Sciences Division of the Special Libraries Association. It is currently the most widely read journal among practicing American pathologists.